PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE LATIHAN PADA PEMBELAJARAN MATEMATIKA PENGURANGAN PECAHAN KELAS V SDN 101768 TEMBUNG KAB. DELI SERDANG - Zuraidah Zuraidah (JURNAL TEMATIK, 2015)
This study aims to determine whether the training method can improve learning outcomes math class V SDN 101 768 Tembung. The problem in this study is whether the training method can improve learning outcomes math class V SDN 101 768 Tembung Percut District of Sei Tuan, Deli Serdang regency. The subject of research to all fifth grade students at SDN 101 768 Tembung totaling 34 people, training method. Research was conducted on a mathematic subject "Reducing Fractions". The tools used to collect data in this study is the observation sheet for teachers, observation sheets for student motivation and list of values. The results showed that the initial conditions, the average value of the student count is 41.76%. In the first cycle the average value calculated that 58.67% of students rose from 41.76% to 58.67%., While in the second cycle there is a very significant rise, the average value of students rose to 85,29s%. The number of students who succeed in the beginning is 7 (20.59%), whereas in the first cycle = 16 (47.05%) increased in the second cycle to 29 people (85.29%).